Customer and Developerâs Point of Views to Game Cloning - Susanto, Ryan (SISFORMA, 2014)
Game Cloning is an action of cloning games. This non-ethical action reaps many controversial matters from game customer and developer in game industry. As a result, this action is considered a wrongdoing. However, but not all cases of game cloning are wrong.Â  Many recent games have been rooted from game cloning. In case of game cloning, game developers do not commit something illegal or immoral since they revamp and complement the games they imitate